Growth Performance, Intestinal Morphology, Cecal Microbiota Community and Ileal Nutrient Utilization of Broiler Chickens Fed Diet Containing Fermented Sesame Meal Using a Mixture of Bacillus subtilis, Lactobacillus Plantarum and Aspergillus Niger - Yaser Salari Telmadarreh; Vahid Rezaeipour; Rohullah Abdullahpour; shahabodin Gharahveysi (Poultry Science Journal)
This study aimed to investigate the efficacy of fermented sesame meal (FSM) utilizing a blend of Bacillus subtilis, Lactobacillus plantarum and Aspergillus niger compared to phytase supplementation on growth traits, jejunal morphology, cecal microbiota activity, and apparent digestibility of nutrients in broiler chickens. A total of 525-day-old male broiler chicks were randomly allocated to seven treatments. Each treatment had five replicate pens of 15 birds in each. The experimental treatments comprised a corn-soybean meal diet (control), a control diet supplemented with 6% or 12% of untreated sesame meal (USM), 6% or 12% of FSM, and 6% or 12% of USM with phytase supplementation. From 1 to 42 days of age, the feed conversion ratio improved in broilers fed diets containing 6 and 12% FSM and USM+phytase (P < 0.05). In the jejunum, morphological indices, the highest villus length, villus width, the ratio of villus length to crypt depth, and villus surface area were observed in broilers that received 6% FSM diet (P < 0.05). In terms of the cecal microbial population, the viable cell counts of Lactobacillus and aerobic total bacteria increased, and the population of E. coli decreased in broilers fed with a diet containing 6% FSM (P < 0.05). Ileal digestibility of ether extract decreased in broilers fed with a diet containing 12% USM, while crude protein digestibility increased in control and 12% FSM groups (P < 0.05). In summary, utilizing FSM or USM+phytase demonstrated improvement in the feed conversion ratio of broilers. Besides, jejunum villi enhancement, increased nutrient digestibility, and an improvement in the cecal microbiota activity were observed in broilers fed with diets containing FSM.